Retrieval-Induced Forgetting as Motivated Cognition - Pica, Gennaro; Chernikova, Marina; Pierro, Antonio; Giannini, Anna Maria; Kruglanski, Arie W. (Frontiers in Psychology, 2018)
Recalling information from a particular category can reduce one’s memory capability for related, non-retrieved information. This is known as the retrieval-induced forgetting effect (RIF; Anderson, Bjork, & Bjork, 1994). The present paper reviews studies that show that the RIF effect is motivated. More specifically, we describe research showing that the need for closure (NFC; the motivation to attain epistemic certainty; Kruglanski & Webster, 1996) generally enhances the RIF, because this prevents uncertainty and confusion from the intrusion of unwanted memories during selective-retrieval. However, when the content of the to-be-forgotten information serves the retriever’s goals, NFC reduces RIF. Overall, the present findings are consistent with the view that motivation can affect the magnitude of RIF effects which, in turn, can serve as a mechanism for reaching preferred conclusions.